PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH DAN PENGAWASAN KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA DENPASAR - Ni Putu Eka Widyastuti; Ni Putu Trisna Windika Pratiwi (UNHI Press, 2021)
The quality of financial reports can be said to be good, if they provide financial statement information that is easy to understand, and can meet the needs required by the user in making a decision, free from misleading meanings, errors in material and can be relied on. The purpose of this study was to determine the effect of the application of government accounting standards (SAP) and financial supervision on the quality of the regional government financial reports of Denpasar city. The data used in this study are primary data using a questionnaire as a method of collecting data obtained from respondents. The population in this study were all employees in OPD in Denpasar City. The method of determining the sample in this study used a purposive sampling method, with the criteria for the sample who held positions as Head of the Finance Subdivision, Expenditure Treasurer and employees who directly carry out accounting functions in OPDs throughout Denpasar City. The sample used in this study were 43 OPDs in Denpasar with 129 respondents. The analysis technique used in this research is Multiple Linear Regression Analysis. The results of this study indicate that the effect of government accounting standards (SAP) and financial supervision has a positive and significant effect on the quality of financial reports for the local government of Denpasar city.